2019
DOI: 10.21608/zumj.2019.10189.10800
|View full text |Cite
|
Sign up to set email alerts
|

Different Endoscopic Approaches Addressing Frontal Sinus

Abstract: Background: Chronic frontal sinusitis as a component of chronic rhinosinusitisis is one of the greatest challenges in rhinology. The endoscopic endonasal approach to the frontal sinus became the standard approach in chronic rhino sinusitis refractory to medical management. Objectives: The aim of this work is to assess different approaches addressing frontal sinus disease in twenty four patients with chronic frontal sinusitis resistant to medical treatment for a period not less than twelve weeks in Otorhinolary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Intact bullae technique had the least duration with a mean of 26.57 ± 1.86 minutes compared to classic approach with a mean of 35.61 ± 2.13 minutes. Also, Mobashir et al (7) discovered a statistically significant distinction in operative time between the two procedures. The average time for the intact bullae procedure was only 26.14 minutes, while the time for the traditional method was 35.47 minutes.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Intact bullae technique had the least duration with a mean of 26.57 ± 1.86 minutes compared to classic approach with a mean of 35.61 ± 2.13 minutes. Also, Mobashir et al (7) discovered a statistically significant distinction in operative time between the two procedures. The average time for the intact bullae procedure was only 26.14 minutes, while the time for the traditional method was 35.47 minutes.…”
Section: Discussionmentioning
confidence: 98%
“…Female represented 72% of patients. Also, Mobashir et al (7) revealed that twenty-four individuals with frontal sinus illness who had failed to improve on medical treatment for at least twelve weeks were studied. Twenty-four patients participated in the research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation